Crowdfunding from the perspective of young people - Hariwibowo, Ignatius Novianto (Journal of Accounting and Investment, 2024)
Research aims: This study aims to identify the dominant factors that make young people interested in joining or using crowdfunding platforms.Design/Methodology/Approach: This research was conducted using the topic method or text analysis with the Social Network Analysis (SNA) approach. Data in the study were obtained by distributing questionnaires to 201 respondents who were young people aged 19 to 22 years.Research findings: The results of this study revealed that the dominant factors attracting young people to use crowdfunding include web technology, ease of use, high rate of return, transparency, and legality. The results of this study indicate that convenience is the primary attraction for young people in transactions. Theoretical contribution/Originality: The results of this study offer indicators that can be used to measure, in particular, the usability variables of web-based crowdfunding platforms in TAM (Technology Acceptance Model). These indicators encompass the amount of return, clarity of business fields and objectives, and transaction security. As for the variables of ease of use, among others, clarity of navigation and information on the web makes users comfortable.Practitioner/Policy implication: The findings of this study imply that Web 2.0 has become a suitable way of interacting with young people. Hence, crowdfunding platform websites need to be designed to support ease of transactions. However, accountability, transparency, clarity of effort, reciprocity, and legality can be effective campaign methods to attract young people to contribute to crowdfunding. Research limitation/Implication: This study used researchers' judgment to interpret the meaning and the relationship between keywords in sentences submitted by respondents in questionnaires.